THE SOCIAL APPROACH TO THE DEVELOPMENT OF UNFAMILIAR TERMS IN ḤADĪṠ AND THE FORMULATION OF THEIR SELECTION CRITERIA FOR NON-ARABIC SPEAKERS - Fauzun Jamal (CMES (Center of Middle Eastern Studies), 2025)
This study explores the historical development of strange words or gārīb al-Ḥadīṡ and the criteria used by early scholars in selecting them. It examines how social and cultural contexts influenced the methodologies of these scholars and proposes updating classical frameworks to better support non-Arabic-speaking communities in understanding the intended meanings of strange words in the hadiths. The research is grounded not only in sociocultural theories of language and knowledge acquisition, but also in adapting traditional criteria to align with contemporary social developments. The study concludes that the expansion of what is considered garīb was shaped by the integrative interactions among diverse populations following the Islamic conquests, as Arabs came into contact with non-Arab peoples—such as the Byzantines, Abyssinians, and others—continuing through to the present day. It further argues that suitable criteria for non-Arabic speakers should involve interpretive translation that ensures clear explanation and contextualization of the meanings of obscure terms, based on classical gārīb al-Ḥadīṡ sources. In some cases, integrating aspects of Arab cultural context may also contribute to a deeper and more accurate understanding.